2009
DOI: 10.4067/s0718-27242009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of an Evaluation Tool to Predict the Probability of Success of Companies: The Innovativeness, Capabilities and Potential Model (ICP)

Abstract: Successful innovation requires management and in this paper a model to help manage the innovation process is presented. This model can be used to audit the management capability to innovate and to monitor how sales increase is related to innovativeness. The model was developed from a study of companies in the high technology cluster around Munich and validated using statistical procedures. The model was found to be effective at predicting the success or otherwise of the innovation strategy pursued by the compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
0
16
0
1
Order By: Relevance
“…Despite the debate going on for decades (Atuahene-Gima 1996), there is vast research confirming the positive relationship between market orientation and innovation (Baker and Sinkula 1999;Greenley 1995;Lewrick 2009;Zhou et al 2005). Lado and Maydeu-Olivares (2001) also argue that adopting market orientation principles affects positively innovation activities, their magnitude, and effectiveness.…”
Section: Market Orientation and Innovationmentioning
confidence: 99%
“…Despite the debate going on for decades (Atuahene-Gima 1996), there is vast research confirming the positive relationship between market orientation and innovation (Baker and Sinkula 1999;Greenley 1995;Lewrick 2009;Zhou et al 2005). Lado and Maydeu-Olivares (2001) also argue that adopting market orientation principles affects positively innovation activities, their magnitude, and effectiveness.…”
Section: Market Orientation and Innovationmentioning
confidence: 99%
“…(), the existence and occurrence of a firm's dynamic capabilities impact the innovation project portfolio's level of innovativeness. IPPM capabilities are essential for successful innovation and for a high degree of innovativeness (Salavou, ; Lewrick, ; Talke et al., ). We conclude:…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…Some scholars have concentrated on suggesting how to develop network relationships and capabilities to achieve innovation success. For example, Lewrick ( 2009 ) emphasized the need to assess the company's current use of crucial capabilities and suggested that fi rms learn from more successful companies. Hussler and Rondé ( 2009 ) suggested that fi rms should build network relationships actively: it is not enough just to move to a region with many top universities and creative fi rmsthese fi rms and universities should also be contacted and possible cooperation opportunities be discussed with them.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…Innovation failure may be caused by the lack of capabilities for organizational • transformation (Herrmann et al 2007 ) . More capabilities are needed for incorporating innovation at all organizational • levels rather than for just developing a new product (Lewrick 2009 ) . Small fi rms are affected by innovation failure more strongly than large ones, as • due to the lack of resources they only have a few R&D projects, while large fi rms quite often have more (Rammer et al 2009 ) .…”
Section: Literature Reviewmentioning
confidence: 99%